Safety assessment of drotrecogin alfa (activated) in the treatment of adult patients with severe sepsis - Gordon R. Bernard; William L. Macias; David E. Joyce; Mark D. Williams; Joan Bailey; Jean‐Louis Vincent (2003)
Abstract Introduction Drotrecogin alfa (activated; recombinant activated protein C) was shown to reduce 28-day all-cause mortality in patients with severe sepsis and to have an acceptable safety profile in 1690 patients studied in the F1K-MC-EVAD (PROWESS) trial. We analyzed all available data on the safety of treatment with drotrecogin alfa (activated) in 2786 adult patients with severe sepsis enrolled in all phase 2 and 3 clinical trials, and in an estimated 3991 patients receiving the drug in commercial use. Patients and method Mortality and safety analyses were performed on all available data from adult severe sepsis patients enrolled in seven clinical trials as of 12 April 2002. Trial-specific safety data and spontaneously reported serious adverse events from commercial use were extracted from a pharmacovigilance database. Results The 28-day mortality rate for all adult patients who received active treatment in all clinical trials was 25.3% (704/2786). Serious bleeding events during the infusion period and 28-day study period occurred in 2.8% (79/2786) and 5.3% (148/2786) of patients, respectively. Of bleeding events during the infusion period, 43% (34/79) were procedure-related. Fatal serious bleeding events during the infusion period occurred in 0.4% (12/2786) of cases. Intracranial hemorrhage (ICH) events during the infusion period and 28-day study period occurred in 0.6% (16/2786) and 1.1% (32/2786) of patients, respectively. Ten out of the 16 ICH events occurring during the study drug infusion period were associated with severe thrombocytopenia (≤ 30,000/mm 3 ) and/or meningitis. Serious bleeding and ICH events spontaneously reported from commercial use ( n = 3991) occurred in 0.9% and 0.2% of patients, respectively. Conclusion Drotrecogin alfa (activated) significantly reduces mortality in severe sepsis. The efficacy and safety profiles of drotrecogin alfa (activated) have remained consistent over the conduct of multiple clinical trials. The most important serious adverse event associated with drotrecogin alfa (activated) treatment is bleeding. Additional clinical experience indicates that invasive procedures are associated with a substantial percentage of serious bleeding events, particularly those occurring at the start of infusion of the drug. Severe thrombocytopenia (for all serious bleeding events, including ICH) and meningitis (for ICH only) may be risk factors for serious bleeding. However, patients with severe thrombocytopenia and/or meningitis may be at greater risk for bleeding or ICH in the absence of drug therapy.